Isolation of nitrogen-fixing bacteria from soil samples - Lim, Zhen Fei (2015)
The isolation of nitrogen fixing bacteria was carried out from two types of soil samples which are municipal waste soil sample and agricultural soil sample. Isolation was done on nitrogen free medium where in first batch all Norris medium was used and result shows slow growth rate. Burks medium was used in replacing Norris medium and higher growth rate was observed.12 isolates were obtained from Burks medium but only six isolates were selected for further study based on their different morphological characteristics observed. Morphological characterizations of the six isolates were done on nutrient agar based on colony shape. Certain isolates showed similar characteristic with Azotobacter vinelandii. Other isolates showed unique characteristics in shape and color. Three isolates were shown to be Gram Positive and the other three to be Gram Negative. Two of the six isolates were selected to undergo molecular characterization where one sample is from agricultural soil and the other from municipal waste soil. DNA of bacteria was extracted using G-spin extraction kit. Band of both isolates can be observed but in a low yield mostly due to the thick cell wall of Gram positive sample. Amplification of 16S rDNA was done using polymerise chain reaction (PCR) technique and the band of both isolates can be observed at a range of 1,000 to 1,500 bp. nifH gene were amplified and bands of both isolates were obtained at range of 90 to 100 bp. DNA samples were purified using DNA purification kit